Sparus aurata escapes from offshore fish farms around Madeira - Müller, Johannes (2019)
In Madeira, an archipelago situated in the North Eastern Atlantic, Sparus aurata was recorded in the wild shortly after the introduction of this species to offshore farming facilities in 1997. In this study, oceanographic and maintenance data of fish farms from Madeira was gathered to evaluate the most relevant factors behind the escapes of Sparus aurata. The community of fish associated with the farming facilities was analysed with the help of an underwater camera-system. Also, previously escaped specimens of S. aurata were caught in the wild, followed by stomach content analysis. Archive data from regular inspection dives from the Calheta offshore fish farm was analysed with corresponding data on sea conditions. Results point towards the relevance of extreme weather and sea conditions and related structural failure for fish escapes; a significant correlation was found between wave height and the amount of recorded net-damage at the fish farming facilities. However, certain damage was unlikely caused by structural failure and may be the result of predator attack or other causes. Notwithstanding the above, the abundance of top carnivorous species (e.g. Seriola spp., Pomatomus saltatrix and Spyraena viridensis) appeared to be low and an analysis of underwater footage revealed, that the most abundant species around the farm were Trachinotus ovatus and Sardinella maderensis. An examination of 38 escapee seabream caught in the harbour of Calheta indicated, that S. aurata preferably feed on fish and the diet appears to differ substantially from conspecifics within the native distribution range. All sampled animals were considered sexually immature, not providing evidence for the existence of a self-sustaining population of S. aurata in the wild. Future research is necessary to fully comprehend all relevant factors involved in the escapes of S. aurata from Madeiran fish farms and to further assess possible impacts of the species on the local ecosystem.